2010
DOI: 10.1002/jqs.1282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of detrital carbonate on stable oxygen and carbon isotope data from varved sediments of the interglacial Piànico palaeolake (Southern Alps, Italy)

Abstract: Naumann, R. 2010. Effects of detrital carbonate on stable oxygen and carbon isotope data from varved sediments of the interglacial Piànico palaeolake (Southern Alps, Italy).ABSTRACT: Contamination with detrital matter is a well-known bias in d 18 O records from lake carbonates but quantitative information of this effect is yet lacking. Therefore, we developed a new methodological approach combining isotope analyses with microfacies, X-ray diffraction and micro-X-ray fluorescence data and applied this in a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
(31 reference statements)
1
18
0
Order By: Relevance
“…A bias of the δ 18 O calcite record through isotopically enriched detrital carbonates from the catchment (Leng & Marshall 2004) is excluded, as microfacies analysis proved the endogenic origin of the measured calcite (cf. Mangili et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bias of the δ 18 O calcite record through isotopically enriched detrital carbonates from the catchment (Leng & Marshall 2004) is excluded, as microfacies analysis proved the endogenic origin of the measured calcite (cf. Mangili et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A bias of the d 18 O calcite record through isotopically enriched detrital carbonates from the catchment (Leng & Marshall 2004) is excluded, as microfacies analysis proved the endogenic origin of the measured calcite (cf. Mangili et al 2010). Furthermore, effects of the epilimnetic water temperature during calcite precipitation on the d 18 O calcite record can be ruled out because of the parallel course of the d 18 O ostracods record, which is independent of seasonal changes in surface water temperature (von Grafenstein 2002).…”
Section: ) Deciduous Trees and Particularly Ulmus Andmentioning
confidence: 99%
“…Consequently, 46 varves were omitted from the sampling, in order to avoid a bias of the stable isotope data through detrital carbonate (Mangili et al, 2010). Thirty-three of these varves occurred in the 352 varve interval at the beginning of the PMO, and the remaining 13 in the sampled interval at the end of the PMO.…”
Section: Sampling For Isotope Analysesmentioning
confidence: 99%
“…It is proposed that contamination by detrital carbonate is not an issue at Tirinie for three reasons. Firstly, several authors have suggested that isotopic datatsets derived from carbonate subsamples that are affected by varying degrees of detrital contamination typically show a strong degree of co-variance between d 18 O and d 13 C (Leng et al, 2010;Mangili et al, 2010), a pattern that is not seen in the Tirinie dataset (¼ r 2 ¼ 0.126, see Supplementary Information 1). Secondly, the process of sieving removed any carbonate material >63 mm, meaning that the analysed carbonate should be dominated by the fine-grained endogenic fraction.…”
Section: Interpretation Of the D 18 O And D 13 C Signalmentioning
confidence: 99%